Development of microcontroller-based inverter control circuit for residential wind generator applications - Ahmad Zaidi, Ahmad Firdaus; Muhida, Riza; Ahmad Zaidi, Ahmad Mujahid; Yaacob, Sazali; Ahmad Zaidi, Nur Hidayah (Penerbit UTHM, 2010)
The current usage level of wind power as alternative source of energy in Malaysia is very low. Ironically, some areas particularly coastal area has steady wind energy supply that is potential to generate electricity for residential use. There is urgent need to locally develop the low cost wind turbine generator that has the capability to not only supply electricity to respective household but can be connected to power grid so that excess power could be sold back to the local utility company. Recent developments of power electronic converters allow stable supply needed for grid transfer in respect to nature of wind dynamics, enhanced power extraction and low total harmonic distortion (THD). In this project, an inverter circuit with suitable control scheme design is developed to be used with a 500W permanent magnet type wind generator which is typical for residential use. Expected circuit output is single phase 240V sine wave voltage which is nominal grid voltage with the total harmonics distortion (THD) of voltage across load should not exceed 5% as recommended by IEEE Standard 519-1992. The simulation and experimental results are included in the paper.